Contagem automática tridimensional dos folículos ovarianos durante o ciclo menstrual - Castro, Eduardo Camelo de (2015)
OBJECTIVES: To evaluate the variability of three-dimensional automatic counting of follicles measuring between 2 - 6 mm and 2 - 10 mm during the menstrual cycle. Considering that this is a standard exam for the early follicular phase, to check if this test can be applied during other phases of the ovarian cycle. METHODS: A Prospective observational study. Serial transvaginal ultrasound scans were performed from 04/20/2013 to 10/30/2014 on infertile patients. Inclusion criteria included age between 18 and 35 years, body mass index 18-25 kg / m2, regular menstrual cycles, no history of ovarian surgery and no hormonal changes to TSH, prolactin, fasting insulin and fasting glucose. Those patients with ovarian cysts or who did not complete one or more days of the serial transvaginal ultrasound scans and who did not undergo three-dimensional (3D) scanning with the researcher, were excluded. The antral follicle count was taken in 3D mode with automated software. Visits were scheduled for early follicular (2 to 5 days), mid-follicular (days 6 - 10), periovulatory (days 12 - 16) and luteal (days 20 - 26) phases of the menstrual cycle. RESULTS: Forty-five women were included. The Friedman test showed that the total number of antral follicles measuring 2-6 mm varied significantly (p=0.001) across the four periods of the menstrual cycle. The Paired Student’s t-test showed a significant increase in follicles count 2-6 mm from the mid-follicular and periovulatory to the luteal phase. We found no significant intracycle variation between the small antral follicles (2-6 mm) in the early follicular, mid-follicular and periovulatory phases. The Friedman test showed that the total number of antral follicles measuring 2-10 mm varied significantly (p=0.003) across the menstrual cycle. Paired Student’s t-test showed a significant increase in count from the early follicular to the mid-follicular phase. CONCLUSIONS: The variation of three-dimensional automatic follicles counting 2-6 mm in the early follicular, mid-follicular and periovulatory phases was not statistically significant. There was a significant variation in the 3D automatic count of ovarian follicles measuring 2-10 mm during the menstrual cycle. The significant variability in the counting of antral follicles measuring 2-10 mm across the menstrual cycle does not permit this examination to be carried out of early follicular phase.